Complex Systems Design & Management Asia Smart Nations - Sustaining and Designing: Proceedings of the Second Asia-Pacific Conference on Complex Systems Design & Management, CSD&M Asia 2016 - Cardin, Michel-Alexandre; Fong, Saik Hay; Krob, Daniel; Chuen, Lui Pao; Tan, Yang How (Advances in Intelligent Systems and Computing,, 2016)
This book contains all refereed papers that were accepted to the second edition of the Asia-Pacific conference on « Complex Systems Design & Management Asia» (CSD&M Asia 2016) that took place in Singapore from February 24 to February 26, 2016 (Website: http://www.2016.csdm-asia.net/). These proceedings cover the most recent trends in the emerging field of Complex Systems, both from an academic and a professional perspective. A special focus is put on Smart Nations: Designing and Sustaining. The CSD&M Asia 2016 conference is organized under the guidance of the Singapore division of the Center of Excellence on Systems Architecture, Management, Economy and Strategy (CESAMES) - Legal address: C.E.S.A.M.E.S. Singapore - 16 Raffles Quay - #38-03 Hong Leong Building - Singapore 048581 (website : http://www.cesames.net/en - email: contact@cesames.net).